Observation of grating diffraction radiation at the KEK LUCX facility; Scientific Reports; Vol. 10 - Aryshev A.; Potylitsyn A. P. Alexander Petrovich; Naumenko G. A. Gennadiy Andreevich; Shevelev M. V. Mihail Viktorovich; Shkitov D. A. Dmitriy Andreevich; Sukhikh L. G. Leonid Grigorievich; Terunuma N. Nobihiro; Urakawa J. Junji (2020, 2020)
Title screen